Agama dalam Perjalanan Gangguan Mental Psikotik dalam Konteks Budaya Jawa - Subandi, - (Jurnal Psikologi, 2012)
The inter relationship between religion and mental illness is very complex. Religion can be an effective therapy but it can also be the trigger of mental illness. This study aims at exploring religious and spiritual issues among psychotic patients. This study employs a qualitative case study method. The subjects were 7 patients who suffered from a first episode psychotic disorders. They were recruited based on the diagnosis provided by two mental hospitals in Yogyakarta. Data were collected through interviews and observations, either directly to the subject or to the family caregivers. Several themes in this study showed that religion had a role in triggrering psychotic disorder through internal moral conflict and external conflict between particular religious groups and traditions. Some religious issues were also present in the symptoms of psychotic disorder particularly in the content of delusion and hallucination. Meanwhile, religious coping played an important role in the process of recovery. Participants understood that their illness was their destiny (takdir) which had to be accepted (nrimo). Acceptance of participants’ destiny did not associate with fatalistic attitude. On the contrary, their understanding that the illness was from God meant that it could be cured. This understanding provided a light of hope which ignited their effort (usaha) to solve their problem. Keywords: course of mental illness, religion, religious coping